The information leakage strategies of the supply chain under the block chain technology introduction - Li, Qiu-xiang; Ji, Hui-min; Huang, Yi-min (Omega (Oxford), 2022)
•In this paper, we consider two manufacturers and one retailer in a supply chain system, the large manufacturer and the retailer conduct the block chain technical cooperation and the small manufacturer adopts passive and active acceptance strategies. Using signal game theory, this paper studies the production decisions and strategy choices of supply chain members under the revenue sharing contract when information leakage occurs in the supply chain.•The main innovations of this paper are as follows.•Conceptual model innovation. The characteristics of existing research conceptual models are as follows:①information game between the two retailers;②the small retailer has no market demand forecasting ability;③Regard the manufacturer as an information transmission intermediary to leak the order quantity information to the small retailer. The characteristics of this conceptual model are as follows:①information game between the two manufacturers; ②both manufacturers have certain market demand forecasting ability; ③Regard the retailer as an information transmission intermediary to leak the production information to the small manufacturer.•Take blockchain technology into account. Most existing studies analyze blockchain technology from the technical level, ignoring its impact on market demand and the game between supply chain members.This paper studies blockchain's impact on supply chain information sharing and information leakage behavior, and enriches the research on the application of blockchain technology in supply chain.•The active acceptance strategy of information recipients is innovatively proposed. Existing studies suppose that the small retailer (information receiver) has no market forecasting ability and can only passively receive information. In this paper, the information receiver retains a certain market demand forecasting ability, and innovatively proposes an active acceptance strategy for the information receiver. Under the block chain technology introduction, a supply chain consisting of a retailer and two competing manufacturers is studied, in which the retailer realizes the vertical information sharing with one manufacturer (the large manufacturer) and always leaks the production information to another manufacturer (the small manufacturer). The small manufacturer has two strategies: passive acceptance strategy and active acceptance strategy. This paper establishes the decision models of supply chain members based on signal transmission theory, and discusses the influence of information leakage and information distortion on the decisions of supply chain members. The analysis shows that there are two equilibrium strategies for the large manufacturer: separation strategy and pooling strategy, and the strategy choice is related to the fluctuation of market demand and the small manufacturer's strategy choice. The retailer chooses information distortion strategy under high market demand, which reduces the profit of the small manufacturer and maximizes the profits of the retailer and the large manufacturer. In terms of the small manufacturer, an active acceptance strategy is more advantageous. In the end, the research conclusion is verified by numerical simulation, and it is found that the introduction of block chain technology has little influence on the manufacturers’ production decisions, and the large manufacturer' production increases in response to the increasing dependence of the small manufacturer's production decision on the large manufacturer's decision.